2018
DOI: 10.15537/smj.2018.1.21438
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of menstrual problems and their association with psychological stress in young female students studying health sciences

Abstract: Objectives:To identify the prevalence of various menstrual problems in young females studying health sciences and to identify their association with academic stress.Methods:This was a cross-sectional study, conducted in the health colleges of Immam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia between February 2015 and February 2016. Seven hundred and thirty-eight female students aged 18-25 years anonymously completed menstrual problem identification and perceived stress scale questionnaire. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
136
5
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(177 citation statements)
references
References 28 publications
(44 reference statements)
13
136
5
4
Order By: Relevance
“…26,27 The present study revealed that UW females have a significantly higher prevalence of dysmenorrhea as compared to the OB ones. These findings are line with few previous studies.. 8,12,13,28,29 Chauhan et al narrates that all girls of their study group with moderate and severe dysmenorrhea had BMI < 16.5, but a drawback of this study was that 81% of their total study participants were only UW females, and none of the subject was OW or OB. This unequal distribution of subjects in different BMI groups may have caused a bias in the results.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…26,27 The present study revealed that UW females have a significantly higher prevalence of dysmenorrhea as compared to the OB ones. These findings are line with few previous studies.. 8,12,13,28,29 Chauhan et al narrates that all girls of their study group with moderate and severe dysmenorrhea had BMI < 16.5, but a drawback of this study was that 81% of their total study participants were only UW females, and none of the subject was OW or OB. This unequal distribution of subjects in different BMI groups may have caused a bias in the results.…”
Section: Discussionsupporting
confidence: 90%
“…6 Some studies reveal that there is no relationship between BMI and dysmenorrhea, 6,[9][10][11] whereas increased prevalence of PD is documented in underweight (UW) subjects by other authors. 8,12,13 Still some other data is suggestive of a positive association between increased BMI and PD. 14 In addition, the study results of Hong et al provide a U shaped relationship between BMI and PD, indicating that both the UW and overweight (OW) + obese (OB) females are at a higher risk of having PD.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations